2017
DOI: 10.1007/s10067-017-3762-y
|View full text |Cite|
|
Sign up to set email alerts
|

Tubulointerstitial nephritis-induced hypophosphatemic osteomalacia in Sjögren’s syndrome: a case report and review of the literature

Abstract: Sjögren's syndrome (SS) is a chronic autoimmune inflammatory disease that typically affects the salivary and lacrimal glands. Renal involvement is relatively uncommon and may precede other complaints. Tubulointestitial nephritis (TIN) is the most common renal involvement in SS. Osteomalacia occurring as the first manifestation of renal tubular disorder due to SS is very rare. We report a 39-year-old male who presented with polydipsia, polyuria, and multiple bone pain. Bone density test showed severe osteoporos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Tubular involvement can be associated with dysfunction of any part of the renal tubule and can be responsible for polyuropolydypsic syndrome, low molecular weight proteinuria, aminoaciduria, euglycemic glycosuria, acidosis with normal anion gap, hypokalaemia that may be complicated by paralysis or disturbed heart rhythm, hypophosphoremia linked to increased phosphate excretion that may be complicated by osteomalacia, nephrocalcinosis or the formation of recurrent kidney stones [ 228 , 229 ]. More anecdotally, acquired Gitelman or Bartter syndrome has been described, possibly linked to the presence of specific autoantibodies targeting transporters (ie NaCl co-transporter in Gitelman syndrome) [ 228 , 230 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Tubular involvement can be associated with dysfunction of any part of the renal tubule and can be responsible for polyuropolydypsic syndrome, low molecular weight proteinuria, aminoaciduria, euglycemic glycosuria, acidosis with normal anion gap, hypokalaemia that may be complicated by paralysis or disturbed heart rhythm, hypophosphoremia linked to increased phosphate excretion that may be complicated by osteomalacia, nephrocalcinosis or the formation of recurrent kidney stones [ 228 , 229 ]. More anecdotally, acquired Gitelman or Bartter syndrome has been described, possibly linked to the presence of specific autoantibodies targeting transporters (ie NaCl co-transporter in Gitelman syndrome) [ 228 , 230 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Hypophosphatemia may lead to acquired hypophosphatemic osteomalacia, a disease of bone metabolism which presents with bone pain, weakness and increased susceptibility to fractures. In one review, 38 cases of pSS presenting with osteomalacia were reported (20). Most of these patients developed osteomalacia in the setting of dRTA, although few suffered from Fanconi's syndrome.…”
Section: Testing For Renal Dysfunction In Sjogren's Syndrome: From Scmentioning
confidence: 99%
“…We did not investigate for the presence of renal tubular acidosis (RTA), even if it has been reported to be associated with bone mineral disorders. If release of phosphate and calcium is accelerated with acidosis, it can be employed as a buffer [ 5 ]. RTA can affect the response to calcitriol in bone and also decrease calcium reabsorption, which can occur in long-term osteomalacia.…”
Section: Discussionmentioning
confidence: 99%